Development of a near-transparent and low-cost liquid antenna - Tan, Wei Yang (2024)
This study presents an innovative approach to antenna design, exploring the potential of low-cost and near-transparent liquid antennas for modern wireless communication. It provides a comprehensive historical background on antenna technology, tracing its evolution from its early stages to its current role in 5G networks. The research then delves into developing near-transparent liquid antennas, significantly departing from traditional designs. The study introduces two distinct antenna models using novel methodologies and materials such as ethyl acetate and water. CST software simulations evaluated these models based on their dielectric properties, cost-efficiency, and performance. The ethyl acetate DRA (Dielectric Resonator Antenna) has a ground measuring 61.99 mm in width and 61.99 mm in length, with a cylinder height of 40.06 mm. Similarly, the distilled water DRA has a ground measuring 40.01 mm in width and 40.01 mm in length, with a cylinder height of 17.66 mm. The ethyl acetate DRA and distilled water DRA exhibit resonant frequencies of 2.408 GHz and 2.4 GHz, respectively, with simulated maximum gains of 5.13 dBi and 4.13 dBi. Moreover, the study highlights the transparency of these liquid antennas, noting a minor reduction in light intensity compared to conventional DRAs. The ethyl acetate DRA and distilled water DRA reduce only 20% in light illumination, as opposed to the 70% reduction seen with conventional DRAs. Furthermore, the practical application of these antennas is demonstrated through integration into a Web-Connected Smart Lighting system. This application enables wireless lighting control via a web server, showcasing the proposed antenna design’s functionality, cost-effectiveness, and aesthetic appeal.